2021
DOI: 10.1080/23746149.2020.1870560
|View full text |Cite
|
Sign up to set email alerts
|

Topological insulators-based magnetic heterostructures

Abstract: The combination of magnetism and topology in magnetic topological insulators (MTIs) has led to unprecedented advancements of time reversal symmetry-breaking topological quantum physics in the past decade. Compared with the uniform films, the MTI heterostructures provide a better framework to manipulate the spin-orbit coupling and magnetic/spin properties. In this review, we summarize the fundamental mechanisms related to the physical orders host in (Bi,Sb) 2 (Te,Se) 3 -based hybrid systems. Besides, we provide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 105 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…The two types of magnetic defects, including Ising symmetry ( J z S a 0 and J AE S = 0) and xy symmetry ( J z S = 0 and J AE S a 0), enable different patterns of spin-polarized currents. 46,52,53 The formalism of bond current allows for the computation of physically measurable spatial profiles of local current within the TIs in the non-equilibrium condition. The spin-resolved bond current is calculated using the equations-of-motion approach for nonequilibrium Green's functions 54…”
Section: Model and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two types of magnetic defects, including Ising symmetry ( J z S a 0 and J AE S = 0) and xy symmetry ( J z S = 0 and J AE S a 0), enable different patterns of spin-polarized currents. 46,52,53 The formalism of bond current allows for the computation of physically measurable spatial profiles of local current within the TIs in the non-equilibrium condition. The spin-resolved bond current is calculated using the equations-of-motion approach for nonequilibrium Green's functions 54…”
Section: Model and Methodsmentioning
confidence: 99%
“…The two types of magnetic defects, including Ising symmetry ( J z S ≠ 0 and J ± S = 0) and xy symmetry ( J z S = 0 and J ± S ≠ 0), enable different patterns of spin-polarized currents. 46,52,53…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead one typically has πT ∼ m D and the relevant hierarchy of scales is 1/a 0 πT, m D E, where a 0 is the Bohr radius. In this case it can be shown that the quantum evolution is Markovian, with the local medium relaxation time being shorter than both the time scale associated with internal transitions and the probe (heavy quarkonium) relaxation time [5][6][7]. As a consequence, the dynamical equation which governs the evolution of the heavy quarkonium reduced density matrix is of Lindblad form [1,2].…”
Section: Introductionmentioning
confidence: 99%